The NEW Lodi Declaration on Rural Health. Adopted by the International Congress on Rural Health (ICRH) and the 4th International Conference Ragusa Safety Health Welfare in Agriculture, Agro-Food and Forestry Systems (Ragusa SHWA) - Colosio, Claudio; Schillaci, Giampaolo; Pekez Pavlisko, Tanja; Hannich, Hans Joaquin; Shintani, Shuzo; Takala, Jukka; van der Laan, Gert (La Medicina del Lavoro, 2016)
Whereas more than 50% of the world’s population live in rural areas, with limited or no access to primary health care, basic occupational health care, clean water and sanitation, Whereas unsustainable and unhealthy agricultural practices have influence on the rural population, with potential severe influence on the environment, wildlife, and urban population, through contaminated soil, water and food. [...]